2011
DOI: 10.1371/journal.pgen.1002259
|View full text |Cite
|
Sign up to set email alerts
|

Germline Genetic Variants Disturbing the Let-7/LIN28 Double-Negative Feedback Loop Alter Breast Cancer Susceptibility

Abstract: Previous studies have shown that let-7 can repress the post-transcriptional translation of LIN28, and LIN28 in turn could block the maturation of let-7, forming a double-negative feedback loop. In this study, we investigated the effect of germline genetic variants on regulation of the homeostasis of the let-7/LIN28 loop and breast cancer risk. We initially demonstrated that the T/C variants of rs3811463, a single nucleotide polymorphism (SNP) located near the let-7 binding site in LIN28, could lead to differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 37 publications
(63 reference statements)
1
38
1
Order By: Relevance
“…MiRNAs include primary, precursor and mature miRNA, in which single nucleotide polymorphisms (SNPs) of these miRNAs may improve miRNA binding affinity and change mRNA expression levels of the target genes, thus leading to cancer susceptibility (Liu et al, 2011;Chen et al, 2011). Zhou (2010) and Shi found that the pri-miR-218 rs11134527 SNP was significantly associated with the risk of cervical carcinoma in Chinese women.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs include primary, precursor and mature miRNA, in which single nucleotide polymorphisms (SNPs) of these miRNAs may improve miRNA binding affinity and change mRNA expression levels of the target genes, thus leading to cancer susceptibility (Liu et al, 2011;Chen et al, 2011). Zhou (2010) and Shi found that the pri-miR-218 rs11134527 SNP was significantly associated with the risk of cervical carcinoma in Chinese women.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer cell lines (MDA-MB-468, MDA-MB-231, MCF7, ZR-75-1, BT-474, MDA-MB-435, SK-BR-3 and Hs578T), normal breast MCF-10A cells and 293T cells were obtained from the American Type Culture Collection (Manassas, VA, USA) and maintained in complete growth medium as described previously 39,47 . Liquid nitrogen stocks were created upon receipt, and cells were maintained until the start of each study.…”
Section: Methodsmentioning
confidence: 99%
“…SNPs are the major type of human genomic variation. Among Han Chinese woman, three SNPs (rs4659441, rs3811463 and rs6697410) were detected in the 3'UTR of Lin28, and allelic variation of rs3811463 influenced let-7-related regulation of Lin28 expression (12). Previous studies showed that insulin resistance and defects in insulin secretion play key roles in the etiology of both GDM and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…A SNP located near the let-7 binding site in Lin28, the T/C variants of rs3811463 could lead to differential regulation of Lin28 by let-7 (12). The rs3811463 polymorphism in the let-7/Lin28 pathway significantly increased the risk of T2DM (13).…”
Section: Introductionmentioning
confidence: 99%